Respostas

2014-07-01T17:10:48-03:00
 f(1)=-3 e f(-2)=-12
a + b = -3
-2a + b = -12

b = -3 - a

-2a - 3 - a = -12
-3a = -12 + 3
-3a = -9
a = 3

b = -3 - 3
b = -6

y= 3x - 6

f(7)=3(7) - 6
        21 - 6
          15

Resposta letra e)
2014-07-01T17:20:13-03:00
A resposta dá 15..

1°) y = ax + b,  para x= 1 e y = -3
     a+b=-3
 
2°) y = ax + b, para x = -2 e y = -12
       -2a+b=-12

3°) resolva o sistema 1 e 2...e encontrará  a = 3 e b = -6

4°) depois é só calcular f (7).

então f(7)= ax + b substitua a e b 
          f(7)= 3 * 7+ (-6)
    
          f(7) = 15.